P16INK4A Immunohistochemistry as a Gold Standard for Cervical Cancer and Precursor Lesions Screening - Mahdieh FARZANEHPOUR; Ahad MUHAMMADNEJAD; Setareh AKHAVAN; Amir Nader EMAMI RAZAVI; Somayeh JALILVAND; Vahid SALIMI; Ebrahim FAGHIHLOO; Ehsan KAKAVANDI; Mohammad FARAHMAND; Mohammad SHAYESTEHPOUR; Farzad BABAKHANI; Talat MOKHTARI AZAD (Tehran University of Medical Sciences, 2020)
Background: High-risk (HR) Human papillomaviruses (HPVs) are known as the main factors implicated in the pathogenesis of cervical preinvasive and invasive lesions. Therefore, the presence or absence of HR-HPV can be followed for the prognosis of low-grade and high-grade squamous intraepithelial lesions. Since the overexpression of p16INK4a protein depends on the presence of transcriptionally-active HPV, and due to its availability and simple interpretation, it may be considered as a proper marker to diagnose cervical cancer. Methods: An immunohistochemical analysis of p16INK4a was performed in 72 cervical tissue specimens at Imam Khomeini Complex Hospital (Tehran, Iran) from 2016 to 2018. The performance parameters were calculated and compared using receiving operating characteristics curve (ROC) details. Results: p16INK4a is significantly up-regulated in the cervical cancer samples in comparison with that in normal samples. Moreover, the ROC data showed the potential ability of p16INK4a under determined conditions as a diagnostic marker for CIN 2-3 staging and invasive cervical cancer. The molecular typing disclosed the attendance of HPV DNA in 44.4% of cases (32/72) with a predominance of HPV type 16. Conclusion: The molecular biomarker p16INK4a can be a good candidate for the early diagnosis and prognosis of cervical cancer in HPV-infected patients. Considering the increase in the expression level of p16INK4a in cancer and precancer tissues, p16INK4a may be used for early detection of cervical cancer.